2016
DOI: 10.15406/mojwh.2016.03.00058
|View full text |Cite
|
Sign up to set email alerts
|

Titrated Oral Misoprostol as a Safe Route for Induction of Labour at Term (A Clinical Trial)

Abstract: Objective: To assess safety and efficacy of induction of labour at term by low doses of oral misoprostol in the form of titration versus the standard regimen of vaginal misoprostol in the term of induction delivery interval, operative interventions and fetal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…Kahdija et al [35] induced labor in pregnant women with a medical indication for induction and had found a rate of 41% of cesarean sections in a series of 100 pregnant women after induction with 50 µg of oral Misoprostol every 4 hours. However, Saleh HS et al [34] found a rate of 4% of caesarean section following the same protocol in pregnant women with term pregnancy without medical indication for induction of labor which can be in the same limits than our series.…”
Section: Evolution Of Labor and Maternal Prognosissupporting
confidence: 67%
See 3 more Smart Citations
“…Kahdija et al [35] induced labor in pregnant women with a medical indication for induction and had found a rate of 41% of cesarean sections in a series of 100 pregnant women after induction with 50 µg of oral Misoprostol every 4 hours. However, Saleh HS et al [34] found a rate of 4% of caesarean section following the same protocol in pregnant women with term pregnancy without medical indication for induction of labor which can be in the same limits than our series.…”
Section: Evolution Of Labor and Maternal Prognosissupporting
confidence: 67%
“…During labor, the rate of pathological modification of FHR was 2.9% (2 fetus). This rate is not different from that found by Saleh HS et al [34] which was 2%. 64 (94.1%) newborns had an Apgar ≥ 7 at the first minute versus 4 (5.9%) who had a low Apgar.…”
Section: Perinatal Prognosiscontrasting
confidence: 52%
See 2 more Smart Citations
“…There was one perinatal death in a woman, past dates with oligoamnios and IUGR, had a vacuum delivery for non reassuring fetal heart rate but the baby had intrapartum hypoxia and died 20 minutes after birth. Saleh suggests that oral misoprostol in small, repeated doses in the form of titration has more efficacy and safety and associated with a low incidence of uterine hyperstimulation, low caesarean section delivery rate than vaginal misoprostol for induction of labour at term with unripe cervix [13] . Antil has commented that low dose oral misoprostol solution in titrated doses can be used as a safe and effective alternative in induction of labour as it has lower uterine hyperactivity with good neonatal outcome.…”
Section: Discussionmentioning
confidence: 99%